1994
DOI: 10.1128/mcb.14.4.2235-2242.1994
|View full text |Cite
|
Sign up to set email alerts
|

Multiple cis-Acting Targeting Sequences Are Required for orb mRNA Localization During Drosophila Oogenesis

Abstract: The targeting of positional information to specific regions of the oocyte or early embryo is one of the key processes in establishing anterior-posterior and dorsal-ventral polarity. In many developmental systems, this is accomplished by localization of mRNAs. The germ line-specific Drosophila orb gene plays a critical role in defining both axes of the developing oocyte, and its mRNA is localized in a complex pattern during oogenesis. We have identified a 280-bp sequence from the orb 3' untranslated region capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…For the experiment, we selected the 3′UTR from the orb gene, which encodes the other Drosophila CPEB protein. Like orb2, its mRNA has localization signals and it also has functions in LTM formation [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the experiment, we selected the 3′UTR from the orb gene, which encodes the other Drosophila CPEB protein. Like orb2, its mRNA has localization signals and it also has functions in LTM formation [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…The same picture was observed in orb2 orb flies-i.e., their STM and MTM formation was normal (Figure 1B). Thus, we found that different sequences of the 3′UTR of the orb2 mRNA did To provide further evidence that the proper localization/regulation of orb2 mRNA is critical for LTM formation, we replaced the deletion with two different UTR sequences, the αTub84B tubulin gene 3 UTR, which contains a single consensus CPE sequence, and the 3 UTR that belongs to the orb, another CPEB gene, and contains eight CPEs [34,38]. The full sequences are presented in Materials and Methods.…”
Section: Introduction Of Different Sequences In Orb2 R Allele Does No...mentioning
confidence: 99%